Mavabyi ya ku wa: the prevalence of and risk factors for epilepsy in a rural South African surveillance site - Wagner, Ryan Gregory (My University, 2011)
Epilepsy, a chronic, often treatable condition, is one of the most common neurological conditions globally, with the prevalence of epilepsy significantly higher in developing regions of the world. In 2008, a household survey was undertaken within the Agincourt Health and Demographic Surveillance System (AHDSS) in rural, northeastern South Africa to identify the prevalence of and risk factors for active convulsive epilepsy. A single question was administered as part of the annual census to each household head. This single question sought to identify people with convulsions, while a random sample of 4,500 individuals was drawn from the Agincourt HDSS population as a way to validate the Stage One screening tool. During initial piloting of the Stage One screening question, the question was found to be adequately sensitive and significant (98.3% and 93.1%, respectively). A more specific questionnaire was administered in Stage Two, while a clinical exam and history was performed in Stage Three to conclusively diagnose epilepsy. The adjusted prevalence of active convulsive epilepsy in the three-stage study was 3.26 per 1,000, while the adjusted prevalence in the population sample was 7.72 per 1,000 individuals highlighting a significant difference due to possible methodological or cultural issues. Furthermore, a heterogeneous, random distribution of active convulsive epilepsy was found across the site, with the identification of possible familial clustering in a number of households. By utilizing univariate and multivariate analysis, this study found sex and a family history of seizures to be significant risk factors for developing epilepsy in rural South Africa. Abnormal deliveries and problems after delivery were found to be significant in the bivariate analysis, but not the multivariate analysis. These findings highlight the need for additional research exploring epilepsy in rural South Africa.
M.Sc. (Med.), Faculty of Health Sciences, University of the Witwatersrand, 2011
Keywords: epilepsy; Agincourt, South Africa; convulsive epilepsy